Destabilization of ROR1 enhances activity of Ibrutinib against chronic lymphocytic leukemia in vivo. (January 2020) - Liu, Zhuojun; Liu, Jia; Zhang, Tianming; Shi, Mingxia; Chen, Xiaofang; Chen, Yun; Yu, Jian
Graphical abstract: Abstract: Receptor tyrosine kinase-like orphan receptor 1 (ROR1) is an onco-embryonic antigen presented on chronic lymphocytic leukemia (CLL), but not on normal adult tissues, which promotes CLL-cell survival. Here, ROR1 was identified as a new client of Heat Shock Protein 90 (HSP90) via a mass spectrometry-based screen for ROR1-associated partners followed by co-immunoprecipitation (co-IP) analysis. A binding motif (ELHHPNIV) on ROR1 for HSP90 was revealed, which forms a αC-β4 loop and is necessary for HSP90-facilitated ROR1 stabilization. We also found that targeting HSP90 leads to ROR1 degradation in a ubiquitin-proteasome dependent pathway, by which pro-survival ROR1 signaling was attenuated in CLL. Based on our previous finding that a humanized monoclonal antibody against ROR1 increases the activity of Ibrutinib against CLL, which is currently undergoing evaluation in clinical trials for the treatment of B-cell lymphoid malignancies, we then provided evidence that treatment with HSP90 inhibitor (17-DMAG) enhances anti-CLL activity of Ibrutinib in vitro and in vivo, by down-modulating ROR1. iTRAQ-based quantitative proteomic analysis of other HSP90 oncogenic clients in addition to ROR1, followed by GO/KEGG enrichment analysis, showed that Bruton's Tyrosine Kinase (BTK), B-lymphoid Tyrosine Kinase (BLK), Lymphocyte-specific Protein Tyrosine Kinase (LCK), or LCK/YES-Related Novel Protein Tyrosine Kinase (LYN), as HSP90 clients, were significantly involved in 11 biological processes and 6 signaling pathways. However, immunoblotting validation confirmed that Ibrutinib treatment dramatically deprived HSP90 inhibitors, 17-DMAG, AUY922 or PU-H71, of inducing the degradation of BTK, BLK, LCK or LYN, but not ROR1. Collectively, our data suggested that depletion of ROR1 induced by targeting HSP90 might facilitate the enhancement of Ibrutinib activity against CLL.